Dispensing and quality of Amoxycillin preparations in retail pharmacies on Tanzania market (Tanzania Medical Journal, 2007)
A study on dispensing practice and quality of amoxycillin capsules and syrups was conducted in retail pharmacies in 5 regions of Tanzania. Data on dispensing practice was collected by interviewing 75 dispensers through structured questionnaires. Quality of amoxycillin capsule formulations and dry powder for suspension preparations from six different manufacturers was evaluated for chemical content at the Tanzania Food and Drug Authority (TFDA) in Dar es Salaam. The study showed that of all the dispensers only 17.3% were pharmacists, 21.3% pharmaceutical technicians and 28% were nurses of different ranks. Results indicated that the most dispensed amoxicyllin was the locally produced preparation which accounted for 41.3%. Affordability determined the most dispensed and lowest priced generic brand, amoxycillin by 68%. Results revealed that only 46.6% dispensers refused to dispense amoxycillin without a prescription while 53.4% dispensed. Out of the ones who dispensed, 42.5% gave patients the most expensive preparations and 22.5% just dispensed according to the patients' demands. Similarly patients with prescriptions written in a generic name, the dispensers (28%) issued them with the most expensive brand while others were issued the brand they specifically demanded by 32% of the dispensers. For patients who came to the pharmacy with less money, results revealed that 66.7% of the dispensers dispensed incomplete doses and then requested them to come back for the remainder and 13.3% just gave out incomplete doses without any further counseling. Responses regarding reconstitution of the dry powder for suspension showed that only 10.7% dispensers reconstituted before giving it out to patients and the rest just instructed patients on how to reconstitute at home. Further, 74.7% of dispensers instructed the patients to use teaspoons to measure 5ml of the suspension. The results from the assessment of chemical contents showed that all capsules and dry powder for suspensions complied with respect to pharmacopoeial limits. It is concluded that dispensers should continually undergo continuing education on good dispensing practices. Keywords: Amoxycillin, quality, dispenser, retail pharmacy Tanzania Medical Journal Vol. 21 (1) 2006: pp. 25-27